MOLECULAR BIOLOGICAL DETECTION OF EMERGING TICK-BORNE ZOONOTIC PATHOGENS IN IXODID TICK SPECIES (Mongolian Journal of Agricultural Sciences, 2015)
Tick infestation activity has increased in Mongolia in recent years. Rickettsiosis, ehrlichiosis, Lyme disease and Q fever are all tick borne zoonoses. We aimed to survey dispersal of these zoonotic disease agents in vector tick population by amolecular diagnostic method. In total, 1462 ticks were harbored from various geographical regions of Mongolia. Genomic DNA was extracted from 400 pasture ticks(Dermacentornuttalli, Dermacentordaghestanicus, Hyalommadromedarii, Hyalommaas. asiaticum) and 100 forest ticks (Ixodespersulcatus). PCR was performed to detect zoonotic pathogens and the prevalence of Rickettsia spp., was 12.5 % and 22.9% in pasture and forest tick DNA samples respectively. Ehrlichiaspp., were detected in 28.5 % and 75 % in pasture and forest ticksrespectively. Interestingly, Lyme disease agentBorreliaspp. has not detected in 200 pasture tick DNA samples, but found in one out of 96forest tick DNA samples. Contrary to this, Coxiellaburnetii, the causative agent of Q fever found only in one out of 240 pasture ticksand was not detected in 96 forest tick DNA samples. Results have proven that molecular diagnostic PCR method is the fastest reliable tool to detect zoonotic pathogens in vector ticks.Mongolian Journal of Agricultural Sciences Vol.13(2) 2014:3-7